2014
DOI: 10.1080/15230406.2014.976656
|View full text |Cite|
|
Sign up to set email alerts
|

A comparative analysis of routes generated by Web Mapping APIs

Abstract: Web Mapping APIs (WMAs), such as Google Maps API, are widely used by researchers across different fields to develop geospatial Web applications. Among maps and map functionalities provided through WMAs, route and direction are prominent and commonly available. Given that each WMA uses a different map database and a different set of assumptions, the routes they generate, for the same pairs of origin and destination addresses, are different. Considering the current void in literature on WMAs and the routes they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“… 23 Euclidean and travel distance have been extensively used in previous literature; however, they do not account for traffic patterns, speed limits, and other factors besides distance that may impact an individual’s commute. 61 Web mapping APIs, such as the Google Maps API used for this study, are becoming the more preferred option for transportation and healthcare access analyses because they can account for such factors and, therefore, provide a more realistic estimate of travel time. 61 63 Information on public transit accessibility is rarely incorporated in studies of access to care.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Euclidean and travel distance have been extensively used in previous literature; however, they do not account for traffic patterns, speed limits, and other factors besides distance that may impact an individual’s commute. 61 Web mapping APIs, such as the Google Maps API used for this study, are becoming the more preferred option for transportation and healthcare access analyses because they can account for such factors and, therefore, provide a more realistic estimate of travel time. 61 63 Information on public transit accessibility is rarely incorporated in studies of access to care.…”
Section: Discussionmentioning
confidence: 99%
“…Google produces travel time predictions by tracking Android hand-sets through time and space and processing this data using undisclosed algorithms. Since 2010, only a few studies reported the use of data originating from Google's applications (Wang and Xu, 2011;Socharoentum and Karimi, 2015), although none has verified the accuracy of the reported data which depends on the number of Android hand-sets with location services switched on using a road network, the accuracy of tracking technology and the algorithms used to process the raw data. We must therefore treat with caution the accuracy of the travel time data used in this study, and the variation in this accuracy across the network and over time.…”
Section: Methodology 431 Data Collectionmentioning
confidence: 99%
“…Data models that interact with the geographical structure of cities allow extracting macro-and microscale transport information [20]. As a result, web mapping platforms, such as OpenStreetMap and Google Maps, have emerged for supporting decision making in transport operations [8,21,22]. Ref.…”
Section: Literature Reviewmentioning
confidence: 99%